2005
DOI: 10.1007/s10433-005-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Social engagement and health and social care use and medication use among older people

Abstract: Social engagement has been associated with improved health outcomes in older people, although the precise mechanisms by which this is mediated are not clear. The aim of this study was to examine the relationship between social engagement and health and social care use and medication use in older people. Data were derived from the 1985, 1989 and 1993 waves of the Nottingham Longitudinal Study of Activity and Ageing, a nationally representative sample of people aged 65 and over. Logistic regression models were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 26 publications
0
19
1
3
Order By: Relevance
“…Given the well-demonstrated benefits of fitness and participation in social activities [ 57 ], the older adult’s unmet needs in these domains are worrisome. Possible benefits of such active lifestyles also include reduced mortality [ 61 , 62 ], slower cognitive decline [ 62 ], decreased drug use, reduced use of health services [ 63 ], and reduced depressive symptoms [ 64 ]. As older adults in our study had difficulties in expressing their needs, considering meaning, level of interest and importance of activities could allow a better identification of unmet needs and improving quality of life [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-demonstrated benefits of fitness and participation in social activities [ 57 ], the older adult’s unmet needs in these domains are worrisome. Possible benefits of such active lifestyles also include reduced mortality [ 61 , 62 ], slower cognitive decline [ 62 ], decreased drug use, reduced use of health services [ 63 ], and reduced depressive symptoms [ 64 ]. As older adults in our study had difficulties in expressing their needs, considering meaning, level of interest and importance of activities could allow a better identification of unmet needs and improving quality of life [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent UK study found that social engagement predicted four-(but not eight-) year self-assessed health but not objective health in a cohort of 359 older adults (Bennett 2005). In another study, high social engagement was associated with reduced health service use when analysed cross-sectionally, but was associated with increased use of home help services at 8 year follow-up (Bath and Gardiner 2005).…”
Section: Study Limitationsmentioning
confidence: 97%
“…Zur Feststellung der subjektiven physischen Gesundheit wurde eine modifizierte Version des SF-12 (Physical Component Scale (PCS)) verwendet (Nübling et al 2006;Ware et al 1996), der ein geeignetes Instrument darstellt, um körperliche Funktionen zu erfassen. Eine gute Gesundheit weist einen Zusammenhang mit sozialer Teilhabe auf, indem Sozialkontakte sich positiv auf die Gesundheit auswirken, andersherum stellt jedoch eine gute Gesundheit auch die Voraussetzung für das Aufrechterhalten sozialer Teilnahme dar (Bath/Gardiner 2005). Life Investment als die Bereitschaft, motivationale Energie in Abhängigkeit von der eigenen Entwicklungssituation entsprechend den Bedingungen einzusetzen, die durch die eigene Verfassung und durch den Lebenskontext und die Interaktion zwischen beidem definiert sind (Staudinger/Schindler 2008), wurde in dieser Untersuchung durch eine differenzierte Fragestellung untersucht: So wurden alle Personen befragt, inwiefern diese planend und aktiv Energie in die eigene Gesundheit, das Wohlergehen der Familie, berufsähnliche Tätigkeiten und in die Gestaltung der Freizeit investierten.…”
Section: Messinstrument Und Stichprobeunclassified